THE EFFECT OF COOPERATIVE LEARNING MODEL UPON READING COMPREHENSION OF ELEVEN GRADE STUDENTS OF SMA NEGERI 1 SELONG DIFFERING IN READING INTEREST - ., Pahrurrozi; Marhaeni, A.A.I.N; Dantes, N. (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at finding out the effect of cooperative learning model uponÂ Â reading comprehension of eleven grade students of sma negeri 1 selong differing in reading interest. This study was experimental research used post-test only control group design. This study used random sampling technique involved 84 students who were divided into experimental and control group. Data were collected using questionnaire and test. The data were analyzed two- ways ANOVA and Tukey Test. The result of this research was (1) there was a significant difference between the achievementÂ of the studentsÂ who were taught by cooperative learning model and those who were taughtÂ by using conventional learning model (FA=41,061, p<0,05). (2) There was an interaction between teaching using cooperative learning and conventional model with studentsâ reading interest upon reading comprehension (FAB=0.946 p<0,05). (3)Â for the students with high reading interest, there was a significant difference on the reading comprehension between by using cooperative learning model and conventional learning model (Qhitung=4,119, p<0,05). (4) for the students with low reading interest, there was a significant difference on the reading comprehension between by using cooperative learning model and conventional learning model (Qhitung=2,174, p<0,05). Â Keywords : cooperative learning model, reading comprehension, reading interest